The click-evoked auditory brainstem response is not affected in auditory processing disorder: a meta-analysis systematic review - Maggu, Akshay R.; Yu, Ying; Overath, Tobias (Frontiers in Audiology and Otology, 2024)
Introduction Among several controversies surrounding the field of Auditory Processing Disorder (APD), one of the central unresolved topics is the putative neural origin of APD. More specifically, it is debated whether basic sensory auditory neural processes are affected in individuals with APD. The objective of the current study was to understand whether or not basic sensory auditory neural processes at the level of the brainstem are affected in those with APD. Methods We approached this question by conducting a meta-analysis of studies that compared the Auditory Brainstem Response (ABR) to brief non-speech sounds in individuals with vs. without APD. The ultimate criterion for a study to be included in this meta-analysis was the presence of both APD and non-APD groups on whom ABR waves I, III, and V were collected in response to clicks. In order to extract these studies, a list of inclusion and exclusion criteria were employed during our search using Google Scholar and PubMed databases (accessed between March 2021 and July 2023), resulting in the inclusion of 8 studies. From these studies, we retrieved ABR waves I, III, and V peak amplitude and latency measures. Results Overall, we found no significant differences between those with and without APD on the ABR waves peak latency (wave I: effect size = −0.0365, C.I. = 0.0384; wave III: effect size = −0.0540, C.I. = 0.1417; wave V: effect size = −0.0577, C.I. = 0.1589) and peak amplitude measures (wave I: effect size = 0.0327, C.I. = 0.0473; wave III: effect size = 0.1415, C.I. = 0.1648; wave V: effect size = 0.1281, C.I. = 0.1346). Conclusion These findings suggest that the click-evoked ABR does not seem to be implicated in those with APD.